UTILIZATION OF KEY LOGGER IN SECURITY ASPECT BASED ON SPYWARE FOR MONITORING LAPTOP USING REFOG KEY LOGGER - Chairul Imam; Muhammad Furqon Siregar (INFOKUM, 2021)
Data security in accessing computers and laptops is one form that must be considered both physically and non-physically because Spyware is a program that is able to spy on the activities of computer users and data recording techniques by recording typing or events carried out by a laptop called a keylogger. can also be one of the data security techniques that the user does on the laptop to prevent someone from stealing data on the laptop by using a refog keylogger